Economics of Clusters A Brief History of Cluster Theories and Policy - Vicente, Jérôme (Springer International Publishing, 2018)
'Jérôme gives us cues about what future research should address - first, why successful and wealthy clusters can also be places of poverty, social exclusion and rising inequality, and second, what policies are best to prevent this from happening.' -Elisa Giuliani, University of Pisa, Italy 'This book fills a major gap in the literature on clusters, systematically tracing the history of the cluster concept and incorporating the latest insights in cluster analysis. It is an absolute must-read for any scholar, student and policy practitioner that is interested in clusters.' -Ron Boschma, Utrecht University, the Netherlands and Stavanger University, Norway When we talk about clusters, it's the fabulous destiny of Silicon Valley that first comes to mind - the place where entrepreneurs and policymakers alike flock. But do we really understand the complex mechanics of these clusters? What tools can economics and other related disciplines use to analyze their performance? When it comes to spending taxpayer money to support cluster development, do benefits actually exceed costs? This book provides a synthesis of cluster theory and presents methodologies to analyze their structure and performance. It also contains insights into how to renew regional innovation policy. The French edition of this volume was granted Best Book in Economics 2016 by The French Association of Economics (AFSE) Jérôme Vicente is Professor at Sciences-Po, head of the LEREPS and member of the executive board of the SMS (Structuring of Social Worlds) research unit, all at University of Toulouse, France. .